Teachers' Perspectives on Students' Cultural Diversity: A Systematic Literature Review - Daniela Semião; Maria João Mogarro; Filipe Brás Pinto; Maria José D. Martins; Nelson Santos; Otilia Sousa; Amélia Marchão; Isabel Pimenta Freire; Lucio Lord; Luís Tinoca (MDPI AG, 2023)
Cultural diversity in schools takes on various forms, including social class, ethnicity, religion and nationality, among other factors that constitute students' identity, influencing their learning. Therefore, one of the biggest challenges that educational systems face internationally is the effective inclusion of all children and young people in schools. For this process to be successful, the roles played by teachers are essential. Thus, our main objective with this systematic literature review is to expand knowledge and awareness of cultural diversity issues to promote the inclusion of learners from primary to secondary education in Europe. To achieve this, we will highlight teachers' perceptions of students' cultural diversity and identify a range of strategies and practices that can contribute to the development of their professional learning. The search was conducted in two databases, Scopus and the Web of Science, and focused on articles published between 2010 and 2022. Of the 3976 identified articles, 41 were included in this study. The findings suggest that teachers consider diversity to be a challenge despite the existence of a favorable view toward students' cultural diversity. A set of solutions is given for the development of inclusion processes.